A Transport Theory Development on the Theory of the Value. Issue 6 (18th September 2016) - Giusti, D.; Molinari, V.
ABSTRACT: This work justifies and employs the techniques of Transport Theory for the deeper understanding of the economical problem arisen in the line first developed by Piero Sraffa in the framework of the theory of value and distribution. An integral equation is here proposed for making the model more suitable. This integral equation has been moreover solved both using the Liouville–Neumann series and the Separable Kernel approach. From the solutions obtained, it is possible to calculate the value as a function of the methods of production, the wage, and the rate of profits and to discuss the question of the value of the commodities and the proportions of labor to means of productions.